2012
DOI: 10.1177/1098300712461147
|View full text |Cite
|
Sign up to set email alerts
|

Using SWPBS Expectations as a Screening Tool to Predict Behavioral Risk in Middle School

Abstract: School-wide positive behavior support (SWPBS) focuses on promoting social competence through the establishment of behavior expectations that are explicitly taught and reinforced by all teachers across all settings. This study investigated the validity of using adherence to SWPBS behavior expectations as a screening tool for predicting behavior risk status. A total of 961 students at a middle school serving Grades 6 through 8 were screened using the school’s SWPBS expectations and a standardized norm-referenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Academic progress monitoring, or curriculum-based measurement (Stecker & Fuchs, 2000), such as oral reading fluency has demonstrated effectiveness with students with EBD (Scott & Shearer-Lingo, 2002). Specific to behavior progress monitoring, research also supports the use of daily behavior ratings (Burke, Vannest, Davis, Davis, & Parker, 2009) or daily progress reports (McDaniel, Houchins, & Robinson, 2016). These brief measures combine characteristics of direct observations, which involve collecting data in the time and place where behavior occurs, and rating scales, which indicate changes in behavior, for an easy and valid way of measuring progress toward behavioral goals.…”
Section: Screening and Progress Monitoringmentioning
confidence: 99%
“…Academic progress monitoring, or curriculum-based measurement (Stecker & Fuchs, 2000), such as oral reading fluency has demonstrated effectiveness with students with EBD (Scott & Shearer-Lingo, 2002). Specific to behavior progress monitoring, research also supports the use of daily behavior ratings (Burke, Vannest, Davis, Davis, & Parker, 2009) or daily progress reports (McDaniel, Houchins, & Robinson, 2016). These brief measures combine characteristics of direct observations, which involve collecting data in the time and place where behavior occurs, and rating scales, which indicate changes in behavior, for an easy and valid way of measuring progress toward behavioral goals.…”
Section: Screening and Progress Monitoringmentioning
confidence: 99%
“…The School Wide Positive Behaviour Support expectations has been implemented as screening tool [3] for identifying behavioural risk problems. This screening tool has a five-points Likert scale to evaluate each student according to the Expectations Matrix values.…”
Section: Figure 4 Expectations Matrix Samplementioning
confidence: 99%
“…Within program-wide PBIS, expectation-based behavioral screening may be a viable alternative procedure for initially identifying young children who need additional assessment and behavior support (e.g., skill instruction) due to a lack of program-specific social competence and interfering problem behaviors. Previous studies have documented that expectation-based screening procedures are effective for screening externalizing problems at the elementary and middle school levels (Burke, Davis, Hagan-Burke, Lee, & Fogarty, 2014; Burke et al, 2012). When using expectation-based behavioral screening, the positively worded behavior expectations are used as an initial brief, criterion-referenced screening tool that assesses the degree of adherence to the program-wide behavior expectations.…”
Section: Expectation-based Screeningmentioning
confidence: 99%
“…Expectation-based screening at the preschool level, when implemented within program-wide PBIS, has the potential to offer an additional tool for early childhood educators engaging in behavioral systems change by identifying children who are potentially non-responsive to program-wide efforts. Previous research has found an association between children’s failure to meet program-specific social-behavioral expectations and negative social and behavioral outcomes, especially in the externalizing domain (Burke et al, 2014; Burke et al, 2012). However, research to date has not examined the validity of the expectation-based procedure in the context of program-wide PBIS implementation at the preschool level.…”
Section: Purpose and Research Questionsmentioning
confidence: 99%